Posttraumatic growth and rumination among parents of children with autism spectrum disorder: The mediating role of social support. (October 2022) - Feng, Yongshen; Chen, Kaiyun; Zou, Yuanyuan; Zhou, Xuezhen; Liu, Qian; Zhong, Dongmei; Deng, Tao; Liu, Shaofei; Zhang, Lifeng
Abstract: Although rumination and social support are regarded as essential predictors of posttraumatic growth (PTG), few studies have explored the associations among PTG, rumination, and social support in parents of children with autism spectrum disorder (ASD). This study examined whether social support mediates the relationship between rumination and PTG. Cross-sectional questionnaire data were collected from 385 parents of children with ASD from September 2019 to November 2020 by convenience sampling. Participants completed the Posttraumatic Growth Inventory, Event Related Rumination Inventory, and Social Support Rating Scale. Path analyses showed that subjective support partially mediates the relationship between deliberate rumination and PTG ( β = 0.073, P < 0.001), and indirect effects account for 15.30% of the total effects. In addition, a negative direct path was found between intrusive and PTG because of the suppression effect of subjective support ( β = −0.110, P < 0.01), and indirect effects accounted for 80% of the direct effects. For future studies, it underscores the essential role of subjective support and rumination in promoting PTG in parents of children with ASD. Highlights: Subjective support partially mediated the relationship between deliberate rumination and PTG. Intrusive rumination had a significant direct effect and indirect effect on PTG under the suppression of subjective support. Subjective social support and rumination were essential in promoting PTG in parents of children with autism.